Effect of Temperature on Microbial Communities and Flavor Compounds during the Fermentation of Light-Flavor Baijiu - XIAO Peng, GAO Lu, LI Youming, LI Hehe, WANG Bowen, LIU Mengyao, SUN Baoguo, LI Huifeng (Shipin Kexue)
Light-flavor baijiu is one of the four basic aroma types of baijiu, and the succession and metabolism of the microbial community during the fermentation process is closely related to physical and chemical factors. Fermentation temperature is one of the most important factors. In this study, the fermentation process of light-flavor baijiu at two different initial temperatures, (7.5 ± 1.0) and (15.5 ± 1.0) ℃, was analyzed using Illumina MiSeq sequencing and gas chromatography-mass spectrometry (GC-MS). The results showed that there were significant differences (P < 0.05) in the acidity of fermented grains at different initial temperatures; higher initial temperatures caused a more rapid increase in the relative abundance of Lactobacillus and Saccharomyces in the fermented grains. A total of 62 volatile compounds were detected in the fermented grains, and 12 compounds were identified as important contributors to the differences in the sensory quality of the raw baijiu. Lactobacillus and Saccharomyces were significantly positively correlated with ethyl acetate, ethyl lactate, ethyl 3-phenylpropionate, furfuryl alcohol, ethyl caprate, ethyl butyrate, isoamyl acetate, and isobutyl alcohol and were the key microorganisms contributing to the formation of differential compounds. The microbial community structure and volatile compound composition during the fermentation process of light-flavor baijiu can be effectively regulated by changing the initial fermentation temperature. This study is of great value in guiding the quality control and management strategies during the fermentation process.